Some Operations on Fermatean Fuzzy Soft Matrices - S. Balu, J. Boobalan (Mathematical Statistician and Engineering Applications, 2022)
In this paper,we combine the characteristics of Fermatean fuzzy set with the parameterization of soft matrix and construct the Fermatean fuzzy soft matrix. Some operations such as union, intersection, complement, algebraic difference, algebraic division, meet, join, implication are given and proved some properties using these operations.